Efektifitas desain dan pembelajaran pai dengan strategi Classroom dalam mengembangkani kreativitas mahasiswa - Anis Kurlillah (Fakultas Agama Islam Universitas Al Washliyah, 2025)
This study aims to examine the effectiveness of the design and implementation of Islamic Religious Education (PAI) learning through classroom strategies in enhancing student creativity. In the context of higher education, creativity is an essential competency that needs to be developed so that students not only understand religious theory but also think critically and innovatively in actualizing Islamic values ??in modern life. The classroom strategy approach emphasizes active interaction between students, lecturers, and the learning environment. Through activities such as discussions, case studies, presentations, and projects based on Islamic values, students are trained to develop creative thinking and problem-solving skills regarding social and religious issues. The research findings indicate that the implementation of classroom strategies is effective in fostering various aspects of student creativity, including the ability to generate new ideas, solve problems innovatively, and apply Islamic values ??in real-life contexts. Therefore, the classroom strategy-based PAI learning model is considered relevant to the needs of education in the 21st century.